Infections of the Central Nervous System - Mateusz Dobosz; Klaudia Arciszewska; Aleksandra Bogoń; Jakub Buczkowski; Jakub Maciej Pieniążek; Aleksandra Padkowska; Michał Paprocki; Anna Mataczyńska; Aleksandra Laskowska (Nicolaus Copernicus University in Toruń, 2024)
Central nervous system infections are among the most devastating infections in the world. Pathogens may enter the central nervous system as a result of dissemination from the upper respiratory tract or other primary site via blood and then crossing the blood-brain barrier. Pathogens present in health care facilities are not an exception. In addition, the neurosurgical procedures performed there are an additional way of entering the central nervous system. Moreover, nosocomial infections are characterized by very high morbidity and mortality, therefore their early diagnosis and treatment is important. The aim of the study is to review the current knowledge and guidelines on the most common healthcare-associated infections of the central nervous system, their diagnosis and treatment. Information searches were carried out in online databases, scientific and educational editions. The most common healthcare-associated infection of the central nervous system is meningitis, followed by a subdural empyema and a brain abscess. The greatest risk factor is neurosurgery. In all of the most common infections of the central nervous system listed, rapid implementation of empiric antibiotic therapy is essential. Further antibiotic therapy depends on the identified etiological factor. As a rule, surgical treatment is required for subdural empyema and brain abscesses. Healthcare-related central nervous system infections remain a significant problem. Due to the risk posed by them to the patient's health, prophylaxis, prompt diagnosis and treatment are essential.